2018
DOI: 10.1016/j.cjtee.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of time to surgery from injury on postoperative infection and deep vein thrombosis in periprosthetic knee fractures

Abstract: PurposePeriprosthetic fracture (PPF) is a serious complication that occurs in 0.3%–2.5% of all total knee arthroplasties used to treat end-stage arthritis. To our knowledge, there are no studies in the literature that evaluate the association between time to surgery after PPF and early postoperative infections or deep vein thrombosis (DVT). This study tests our hypothesis that delayed time to surgery increases rates of postoperative infection and DVT after PPF surgery.MethodsOur study cohort included patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Their study also dichotomized the time to surgery at 48 h. Following the statements of Bovonratwet et al, neither mortality nor a variety of different perioperative complications (e.g., urinary tract infection, wound complication, pneumonia) were influenced by a delay in time to surgery [ 16 ]. Similar results were published by Lee and coworkers, who reported 263 patients with TKA suffering from PFF [ 20 ]. Their analysis focused on rates of intra- and postoperative complications dependent on early or delayed surgical treatment.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Their study also dichotomized the time to surgery at 48 h. Following the statements of Bovonratwet et al, neither mortality nor a variety of different perioperative complications (e.g., urinary tract infection, wound complication, pneumonia) were influenced by a delay in time to surgery [ 16 ]. Similar results were published by Lee and coworkers, who reported 263 patients with TKA suffering from PFF [ 20 ]. Their analysis focused on rates of intra- and postoperative complications dependent on early or delayed surgical treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Their analysis focused on rates of intra- and postoperative complications dependent on early or delayed surgical treatment. Additionally, in their patient population the different types of complications remained unaffected by time to surgery at a 48 h cutoff [ 20 ]. Nevertheless, Bhattacharyya et al reported inferior outcomes following delayed surgical treatment in patients with PFF and dichotomization at 48 h [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies reported on transfusion rate with a dichotomised delay to surgery [4,6,7,18]. On meta-analysis, there was a significantly lower transfusion rate for those with an early operation, compared to those with a delay to surgery (RR 0.51; 95% CI 0.31, 0.82; p = < 0.001, Supplementary Fig.…”
Section: Transfusionmentioning
confidence: 98%
“…Mean time to surgery from admission for reporting studies was 64 h. In the two studies that reported dichotomous time to surgery at 24 h [6,7], 46.9% (402/857) and 77.9% (377/484) participants were found to have received surgery within 24 h respectively. Three studies reported dichotomous time to surgery at 48 h [8,18,24], with 31.1% (56/180), 60.1% (409/681), and 216/263 (82%) of individuals receiving surgery within this time frame. All 11 articles included in the study were of a retrospective cohort design.…”
Section: Study Characteristicsmentioning
confidence: 99%